2019
DOI: 10.3389/fpsyg.2019.02409
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Executive Functions, Basic Psychological Needs, Impulsivity, and Depressive Symptoms in American Football Players

Abstract: Executive functions play an important role in sports since the ability to plan, organize, and regulate behavior to reach an objective or goal depends on these functions. Some of the components of executive functions, such as inhibition of impulsive behavior and cognitive flexibility, are necessary for contact sports (e.g., American football) to carry out successful plays on the sports field. Executive functions have been studied in the sporting environment, but their relationship with the athletes’ basic psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 66 publications
1
11
0
7
Order By: Relevance
“…From the point of view of the study of cognitive functions in sports games some authors came to interesting conclusions. Namely, the authors found an improvement in some cognitive and executive functions (inhibition of impulsive behavior and planning) after four months of the season in American football players [27]. However, several factors can come into play, such as personality.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…From the point of view of the study of cognitive functions in sports games some authors came to interesting conclusions. Namely, the authors found an improvement in some cognitive and executive functions (inhibition of impulsive behavior and planning) after four months of the season in American football players [27]. However, several factors can come into play, such as personality.…”
Section: Discussionmentioning
confidence: 96%
“…Open skill sports are characterized by various fast changes in time (position of players in the field), which force the player to reconsider pre-planned actions, inhibit impulsivity in their behavior, anticipate situations in the game and coordinate their movement based on the constant reception of sensorial inputs. Thus, some of the elements of cognition are in high demand in some sports (e.g., any sport game) to ensure the player performs well [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Esse fenômeno também pode ser compreendido, conforme referenciado em três estudos (Mazur et al, 2014;Oprins et al, 2018;Swanson, 2015), segundo a definição de Martin e Rubin (1995) que explica a FC a partir de três características: 1. a consciência de que em qualquer situação há alternativas disponíveis para se comportar; 2. a vontade de ser flexível e de se adaptar às situações; e 3. a autoeficácia em ser flexível. Apesar disso, o que chama a atenção é que, em sete estudos analisados, não há, explicitamente, a descrição da definição e/ou concepção de FC adotada pelos autores (Cropley et al, 2016;Fernández-Sánchez et al, 2018;Hilgert, 1998;Maltese et al, 2016;Rincón-Campos et al, 2019;Roy, 2001;Wykes et al, 2012).…”
Section: Definições De Flexibilidade Cognitiva E Associações a Outros...unclassified
“…Alguns fatores, fenômenos e variáveis foram mais extensamente estudados quanto à sua relação com a FC. Em destaque, alguns artigos selecionados indicaram correlações positivas da FC com: a capacidade de planejamento (Rincón-Campos et al, 2019;Sanchez et al, 2017;Vignochi et al, 2019;Wykes et al, 2012), a capacidade de pensar e agir racionalmente durante o processo de tomada de decisão estratégica (Mazur et al, 2014;Rodríguez-Ponce et al, 2013;Rodríguez-Ponce & Pedraja-Rejas, 2009), a resolução de problemas (Hilgert, 1998;Ong et al, 2019;Sung et al, 2019) e o melhor desempenho em atividades que exijam alternância de tarefas (Montuori et al, 2019;Ong et al, 2019).…”
Section: Definições De Flexibilidade Cognitiva E Associações a Outros...unclassified
“…Therefore, the ability to quickly and accurately predict or perceive relevant information within a limited time in a unpredictable environment facilitates sudden, fast and accurate decision-making, gives the player more time to prepare, and regulate their motor behaviors [11,12]. Performing such actions in complex game sequences that are not previously determined involves high-level perceptualcognitive, and advanced sensorimotor characteristics [10,13,14]. These characteristics are CAT, reaction time, and balance performance.…”
mentioning
confidence: 99%